Luminescent gold–thallium derivatives with a pyridine-containing 12-membered aza-thioether macrocycle. Issue 28 (16th June 2021) - Caddeo, Francesco; Fernández-Moreira, Vanesa; Arca, Massimiliano; Pintus, Anna; Laguna, Antonio; Lippolis, Vito; Gimeno, M. Concepción
Abstract : The heterometallic Tl I /Au I complex {[Au(C6 F5 )2 Tl]2 (L)} n has an unprecedented polymeric structural motif with a metallic pseudo-rhombic Au2 Tl2 core that repeats itself to form zig-zag polymers and shows a thermochromic behaviour. Abstract : The coordination modes of the ligand 2, 5, 8-trithia[9](2, 6)pyridinophane (L ) to thallium(i ), gold(iii ) and gold(i ) have been studied. Thallium(i ) is coordinated by the macrocyclic ligand in [Tl(L)](PF6 ) (1 ) through all the sulfur and nitrogen atoms, in a distorted square-pyramidal geometry with the thallium(i ) ion in the apical position and with the presence of an inert lone pair. Gold(iii ) is bonded by the ligand only through the nitrogen of the pyridine group in [AuCl3 (L)] (2 ), whereas two Au I –C6 F5 fragments coordinate the sulfur atoms next to the pyridine moiety of the ligand in [{Au(C6 F5 )}2 (μ-L)] (3 ), which form a linear polymer through intermolecular aurophilic contacts. The heterometallic Tl I /Au I complex {[Au(C6 F5 )2 Tl]2 (L)} n (4 ) features a polymeric structural nature with a metallic pseudo-rhombic Au2 Tl2 core, which repeats itself forming a zig-zag polymer. In each Au2 Tl2 unit only one thallium atom is bonded by the NS3 donor set of the macrocyclic ligand and also forms two unsupported Au–Tl bonds with two [Au(C6 F5 )2 ] − units in an overall pseudo-octahedral geometry. The other thallium atom similarly bridges the same [Au(C6 F5 )2 ] − units and links a neighbouring Au2 Tl2 moiety, thus exhibiting a distorted trigonal planar geometry being bonded only to three gold atoms with unsupported Au–Tl interactions. This complex displays an interesting thermochromic behaviour showing emissions mainly resulting from MM′CT transitions at room temperature. At 77 K a dual emission appears, probably arising from the two different thallium environments. DFT calculations have been carried out in the attempt to investigate the origin of the emissions of complex 4 .